Mechanism of Action of Prolyl Oligopeptidase (PREP) in Degenerative Brain Diseases: Has Peptidase Activity Only a Modulatory Role on the Interactions of PREP with Proteins? - Männistö, Pekka T.; García-Horsman, J. Arturo (Frontiers in Aging Neuroscience, 2017)
In the ageing brain, the correct balance of neural transmission and its regulation is of particular significance, and neuropeptides have a significant role. Prolyl oligopeptidase (PREP) is a protein highly expressed in brain, and evidence indicates that it is related to aging and in neurodegenration. Althought PREP is regarded as a peptidase, the physiological substrates in the brain have not been defined, and after intense research, the molecular mechanisms where this protein is involved have not been defined. We propose that PREP functions as a regulator of other proteins though peptide gated direct interaction. We speculate that, at least in some processes where PREP has shown to be relevant, the peptidase activity is only a consequence of the interactions, and not the main physiological activity.